. Predictive Value of Pre-delivery Serum β-human Chorionic Gonadotropin, Fibrinogen, and Homocysteine for Hypertensive Disorders of Pregnancy: Predictive Value of Serum β-HCG, FIB, and HCY for HDCP - Zhuo, Miaomiao (Journal of Medical Biochemistry, 2024)
Introduction: it was to investigate the relationship between pre-delivery serumβ-human chorionic gonadotropin (β-HCG), fibrinogen (FIB), and homocysteine (HCY) with hypertensive disorder complicating pregnancy (HDCP). Materials and Methods: 200 HDCP patients and 150 normal pregnant women were selected as study subjects. Fasting cubital venous blood samples were collected to measure serum triglycerides (TG), total cholesterol (TC), high-density lipoprotein (HDL), and low-density lipoprotein (LDL), as well as β-HCG, FIB, and HCY levels. Pearson correlation analysis examined relationship between β-HCG, FIB, HCY, and HDCP. Receiver operating characteristic (ROC) curve analysis evaluated the predictive value of these indicators for HDCP. Multiple logistic regression analysis identified risk factors (RFs) for HDCP.Results: serum TG, TC, HDL, LDL, FIB,β-HCG, and HCY were greatly elevated in the HDCP group versus control group (CG) (P
Keywords: hypertensive disorder complicating pregnancy; β-human chorionic gonadotropin; fibrinogen; homocysteine